A suggested laboratory course in electricity for secondary schools - Biddison, Edna E. (My University, 1908)
Introduction: An examination of the work given in electricity in connection with the Physics Laboratories in a number of the High Schools of the country and a study of the work planned by a number of the best Laboratory Manuals, shows such a wide difference that it has suggested a plan for a Laboratory course which should be a combination between theory and actual practice.
Citation: Biddison, Edna E. A suggested laboratory course in electricity for secondary schools. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Education; Science; Electricity; Laboratory; Graduating theses; Senior theses; Theses